Role of Starch Based Materials as a Bio-sorbents for the Removal of Dyes and Heavy Metals from Wastewater - Haq, Fazal; Mehmood, Sahid; Haroon, Muhammad; Kiran, Mehwish; Waseem, Kashif; Aziz, Tariq; Farid, Arshad (Journal of polymers and the environment, 2022)
Native starch has low adsorption ability due to lack of specific functional groups. To increase the adsorption efficiency of native starch, it needs to be chemically modified. The modification produces specific functional groups on the backbone of starch and increases its adsorption efficacy towards dyes and heavy metals. The modified starch-based adsorbents (succinylated starches, starch phosphate, starch-based composites and nanoparticles, starch-based hydrogels, cross-linked and carboxylated starches and so on) are more useful due to their large surface area, available polar sites and reproducibility in the degree of activation. In this review article we have discussed the application of modified starches as sorbents for the removal of dyes and heavy metals from wastewater. It further highlighted the optimized conditions used for the removal of heavy metals and dyes by the modified starches and the interactions generated between the adsorbent and adsorbate. This article presented the most recent literature and will spark new ideas for researchers working in this field.